Exploring wealth-related inequalities in maternal and child health coverage in Latin America and the Caribbean - Manuel Colomé-Hidalgo; Juan Donado Campos; Ángel Gil de Miguel (BMC, 2021)
Abstract Background Maternal and child health have shown important advances in the world in recent years. However, national averages indicators hide large inequalities in access and quality of care in population subgroups. We explore wealth-related inequalities affecting health coverage and interventions in reproductive, maternal, newborn, and child health in Latin America and the Caribbean. Methods We analyzed representative national surveys from 15 countries conducted between 2001 and 2016. We estimated maternal-child health coverage gaps using the Composite Coverage Index - a weighted average of interventions that include family planning, maternal and newborn care, immunizations, and treatment of sick children. We measured absolute and relative inequality to assess gaps by wealth quintile. Pearson's correlation coefficient was used to test the association between the coverage gap and population attributable risk. Results The Composite Coverage Index showed patterns of inequality favoring the wealthiest subgroups. In eight countries the national coverage was higher than the global median (78.4%; 95% CI: 73.1-83.6) and increased significantly as inequality decreased (Pearson r = 0.9; p < 0.01). Conclusions There are substantial inequalities between socioeconomic groups. Reducing inequalities will improve coverage indicators for women and children. Additional health policies, programs, and practices are required to promote equity.